Association of habitually low intake of dietary selenium with new-onset stroke: A retrospective cohort study (2004–2015 China Health and Nutrition Survey) - Zhang, Huanxiang; Qiu, Hongbin; Wang, Shanjie; Zhang, Yiying (Frontiers in Public Health, 2023)
Background As an essential trace element in the body, selenium is associated with the development of many diseases. The purpose of this study was to explore the association between dietary selenium intake and new-onset stroke risk in Chinese adults. Methods Adults aged ≥18 years in the China Health and Nutrition Survey (CHNS) from 2004 to 2015 were enrolled. Participants were divided into five groups according to the quintile of dietary selenium intake: Q1 (≤ 29.80 μg/day), Q2 (29.80–38.53 μg/day), Q3 (38.53–47.23 μg/day), Q4 (47.23–60.38 μg/day), Q 5(>60.38 μg/day). Cox proportional-hazards model was used to explore the effect of dietary selenium on new-onset stroke. Restricted cubic spline (RCS) was used to visualize the dose-response relationship between dietary selenium and the risk of morbidity. Results A total of 11,532 subjects were included, and 271 (2.35%) of them developed stroke during a mean follow-up of 6.78 person-years. Compared with the lowest selenium intake group, the HR and 95%CI of stroke in the participants with selenium intake of Q2, Q3, Q4 and Q5 were: 0.85 (0.59, 1.21), 0.62 (0.42, 0.92), 0.43 (0.28, 0.68), 0.49 (0.30, 0.82), respectively. There was an L-shaped relationship between dietary selenium and stroke (nonlinear P-value = 0.0420). The HR and 95%CI of developing stroke was 0.75 (0.65, 0.87) in participants with selenium intake ≤ 60 μg/day. Conclusions The L-shaped negative association between dietary selenium and stroke in Chinese adults which indicated that dietary selenium should be improved to a certain level to prevent stroke.